(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The FMS helps in the proper management of financial resources, budgeting, accounting, and reporting of financial transactions. In this research, the focus is on analyzing the impact of FMS on the financial performance of organizations. The study aims to identify the factors that influence the implementation of FMS and how the implementation of FMS affects the financial performance of organizations. Focuses on the development and implementation of a corporate financial management system. This system’s objective is to give stakeholders and business owners accurate and timely financial information so they can make defensible decisions. The study examines current financial management systems in-depth and identifies the essential characteristics and capabilities needed for a successful system. The study showed that the implementation of FMS had a positive impact on the financial performance of organizations. The organizations that implemented FMSs had better financial performance indicators such as profitability, liquidity, and efficiency compared to those that did not implement FMs. The study also revealed that factors such as organizational culture, management support, and technical expertise had a significant influence on the implementation of FMs. The study findings suggest that the implementation of FMS can significantly improve the financial performance of organizations. The FMS enables organizations to have better control and management of financial resources, accurate financial reporting, and efficient budgeting. The study also highlights the importance of factors such as organizational culture, management support, and technical expertise in the successful implementation of FMs. Therefore, organizations need to consider these factors before implementing FMS to ensure the successful implementation and optimal benefits of FMs.